Exploring the Determinants of the Entry and Exit of Ministers in Korea: 1980–2008. Issue 4 (4th November 2012) - Hahm, Sung Deuk; Jung, Kwangho; Lee, Sam Youl
Abstract : The entry and exit of ministers has been of primary interest to students of political science and public management in Western countries. Responding to the lack of research on the entry and exit of ministers in non‐Western countries, this article examined determinants of both the entrance and exit of ministers in Korea from the life cycle point of view based on the Korean Ministerial Database from 1980 to 2008. We argued that as the Korean presidency shifts from an imperialistic to a democratic presidency, ministerial appointments in Korea also seem to shift from an expertise‐focused to a politics‐focused approach. Likewise, the primary resignation reason also shifts from policy failure to political reasons. We also argued that Korean presidents use their power to reshuffle cabinet ministers too often for their political interests. As a result, Korean ministers spend too little time in post; average tenure is now down to about one year. These short terms in office dilute a minister's ability to dictate departmental policy.